2005
DOI: 10.2209/tdcpublication.46.123
|View full text |Cite
|
Sign up to set email alerts
|

Percentile Curves for Food Acceptance Response Scores in Assessing Chewing Functions in Adults

Abstract: The purpose of this study was to evaluate whether percentile curves for food acceptance response scores were useful in assessing oral and occlusal conditions. We used data obtained from Chiba City Patient Surveys (males: 1,276, females: 1,381, aged 20 to 64), which were conducted in 1998 and 1999. Subjects were assigned scores of between 1 and 4 for 31 different kinds of food based on their food acceptance responses. Occlusal conditions were measured with pressure-sensitive sheets. We calculated the percentile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…The deterioration of masticatory performance and salivary flow may lead to changes in the diet, because some foods become troublesome to eat (93, 96, 98–100, 100, 101, 242). A review of the influence of impaired mastication on nutrition has been published some years ago (97).…”
Section: Masticatory Function In Various Groups Of Individualsmentioning
confidence: 99%
“…The deterioration of masticatory performance and salivary flow may lead to changes in the diet, because some foods become troublesome to eat (93, 96, 98–100, 100, 101, 242). A review of the influence of impaired mastication on nutrition has been published some years ago (97).…”
Section: Masticatory Function In Various Groups Of Individualsmentioning
confidence: 99%
“…A self-assessed questionnaire method was prepared using 30 food types to quantify the subjective chewing ability. Seventeen food items were adapted from a previous study (16) and the remaining 13 items were selected from a list of popular Korean foods including: dried filefish, cubed white radish kimchi, roast beef, rib of pork, steamed short ribs, hard boiled burdock, yellow melon, sweet jelly of red beans, mandarin, noodles, watermelon, steamed potato and soybean curd were chosen (19). The FIA questionnaire was formed using a five-point Likert scale: 'cannot chew at all (1 point)', 'difficult to chew (2 points)', 'cannot say either way (3 points)', 'can chew some (4 points)' and 'can chew well (5 points)'.…”
Section: Measurement Of Subjective Fia Scorementioning
confidence: 99%
“…Recently, Sakurai et al. (16) assessed chewing functions in adults using the FIA questionnaire with 31 Japanese foods and stated that this subjective method can be useful in oral health education and clinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have clearly shown that maintaining the number of present teeth (PT) plays a significant role in health-related quality of life in elderly and younger adults 1,2,13,34,40,44,49,50,53,54,62) . More recently, a number of studies have focused on tooth loss as a risk This paper was originally presented as a thesis by T. Kurahashi at the Graduate School of Tokyo Dental College. factor in general health conditions, such as cardiovascular disease and stroke 1,6,8,15,16,19,20,27,29,30,[35][36][37]51,59) , dementia 52) , diabetes mellitus 11,31,41,42,45,56,57) , hypertension 55) , and gastrointestinal cancer 1) .…”
Section: Introductionmentioning
confidence: 99%